2017
DOI: 10.5194/hess-21-6091-2017
|View full text |Cite
|
Sign up to set email alerts
|

Aquifer configuration and geostructural links control the groundwater quality in thin-bedded carbonate–siliciclastic alternations of the Hainich CZE, central Germany

Abstract: Abstract. The quality of near-surface groundwater reservoirs is controlled, but also threatened, by manifold surfacesubsurface interactions. Vulnerability studies typically evaluate the variable interplay of surface factors (land management, infiltration patterns) and subsurface factors (hydrostratigraphy, flow properties) in a thorough way, but disregard the resulting groundwater quality. Conversely, hydrogeochemical case studies that address the chemical evolution of groundwater often lack a comprehensive an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(113 citation statements)
references
References 64 publications
(78 reference statements)
0
105
0
Order By: Relevance
“…The medium 14 C-depleted wells H42, H43, and H52 share low-permeable rocks in laying and hanging strata (Lazar et al, 2019) and are therefore most likely cut off from direct surface-derived inputs, resulting in the moderate 14 C values of DOM in the water from these wells. While H53 had similar characteristics to H52 regarding the 14 C of inorganic carbon (Nowak et al, 2017) and major ion composition (Kohlhepp et al, 2017), DOM showed strong 14 C depletion of in H53 relative to H52. The strong 14 C depletion of DOM in H53 supported the indicated ecosystem compartmentalization by Lehmann and Totsche (2019), who described those zones as hydrogeologically isolated within the shallow groundwater flow system.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The medium 14 C-depleted wells H42, H43, and H52 share low-permeable rocks in laying and hanging strata (Lazar et al, 2019) and are therefore most likely cut off from direct surface-derived inputs, resulting in the moderate 14 C values of DOM in the water from these wells. While H53 had similar characteristics to H52 regarding the 14 C of inorganic carbon (Nowak et al, 2017) and major ion composition (Kohlhepp et al, 2017), DOM showed strong 14 C depletion of in H53 relative to H52. The strong 14 C depletion of DOM in H53 supported the indicated ecosystem compartmentalization by Lehmann and Totsche (2019), who described those zones as hydrogeologically isolated within the shallow groundwater flow system.…”
Section: Resultsmentioning
confidence: 90%
“…The distribution of 14 C values between the wells followed more likely the hydrogeological than the stratigraphic layout of the aquifer system. The wells H31 and H51 are both part of the regional main aquifer that is likely well connected to a large recharge area on the Hainich ridge (Kohlhepp et al, 2017). Compared to the overlying minor groundwater resources, inflow of a relatively larger proportion of surfacederived modern carbon contributing to 14 C-enriched DOM in those wells is therefore probable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Groundwater was collected in the Hainich Critical Zone Exploratory (NW Thuringia, Germany), from shallow groundwater resources in Upper Muschelkalk bedrock that has been extensively described (Küsel et al , 2016;Lehmann and Totsche, 2020) . In brief, the Hainich CZE contains a multistorey, fractured aquifer system within the hillslope, composed of altering layers of limestone and mudstone (Kohlhepp et al , 2017) . The Upper-Muschelkalk aquifer system is characterized by the limestone-dominated main aquifer (Trochitenkalk formation, moTK; formerly referred to as the HTL) that is predominantly oxic and the mudstone-dominated hanging strata (including Meissner formation, moM; formerly the HTU) that is anoxic (Kohlhepp et al , 2017) .…”
Section: Sample Collection Dna Extractionmentioning
confidence: 99%
“…In brief, the Hainich CZE contains a multistorey, fractured aquifer system within the hillslope, composed of altering layers of limestone and mudstone (Kohlhepp et al , 2017) . The Upper-Muschelkalk aquifer system is characterized by the limestone-dominated main aquifer (Trochitenkalk formation, moTK; formerly referred to as the HTL) that is predominantly oxic and the mudstone-dominated hanging strata (including Meissner formation, moM; formerly the HTU) that is anoxic (Kohlhepp et al , 2017) . Groundwater (115 L) was collected from well H52 (moM) on December 11th, 2018 and was sequentially filtered through 0.2 µM, and 0.1 µM PTFE filters (142 mm, Omnipore Membrane, Merck Millipore, Germany).…”
Section: Sample Collection Dna Extractionmentioning
confidence: 99%